2015
DOI: 10.1016/j.icarus.2014.11.039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Poynting–Robertson drag on the triangular Lagrangian points

Abstract: We investigate the stability of motion close to the Lagrangian equilibrium points L 4 and L 5 in the framework of the spatial, elliptic, restricted threebody problem, subject to the radial component of Poynting-Robertson drag.For this reason we develop a simplified resonant model, that is based on averaging theory, i.e. averaged over the mean anomaly of the perturbing planet. We find temporary stability of particles displaying a tadpole motion in the 1:1 resonance. From the linear stability study of the averag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“….67 * 10 −11 × 1.9891 * which is coincident with the results in [6,41]. For other systems, the scaled parameter c will take different values.…”
Section: Dependence Of the Dynamics On Csupporting
confidence: 80%
“….67 * 10 −11 × 1.9891 * which is coincident with the results in [6,41]. For other systems, the scaled parameter c will take different values.…”
Section: Dependence Of the Dynamics On Csupporting
confidence: 80%
“…Then in our system of units the speed of light is equal to c = 22945.23619, for the case of Sun-Jupiter. 23,33 As can be noted, we have assumed that the post-Newtonian contribution to the angular velocity is too small, i.e ω = 1 + ω 1 /c 2 ≈ 1. In order to prove this assumption, let us start by considering that unlike the classical Newtonian system, the post-Newtonian angular velocity depends on the mass parameter µ and the speed of light c, i.e.…”
mentioning
confidence: 99%
“…They found that the effect of perturbation factors are significant. In literature, many researchers have analyzed the photogravitational RTBP in nonlinear sense by considering one or two perturbations at a time (McKenzie and Szebehely 1981;Ishwar 1997;Subba Rao and Krishan Sharma 1997;Lhotka and Celletti 2015;Alvarez-Ramírez et al 2015) but very few of them have considered the problem under the combined influence of few perturbations (Kushvah et al 2007;Kishor and Kushvah 2017). Ishwar and Sharma (2012) have discussed about the nonlinear stability of out of plane equilibrium points in the RTBP with oblate primary and found that L 6 point is stable in nonlinear sense.…”
Section: Introductionmentioning
confidence: 99%